Climate anxiety, wellbeing and pro-environmental action: correlates of negative emotional responses to climate change in 32 countries. (December 2022) - Ogunbode, Charles A.; Doran, Rouven; Hanss, Daniel; Ojala, Maria; Salmela-Aro, Katariina; van den Broek, Karlijn L.; Bhullar, Navjot; Aquino, Sibele D.; Marot, Tiago; Schermer, Julie Aitken; Wlodarczyk, Anna; Lu, Su; et al.
Abstract: This study explored the correlates of climate anxiety in a diverse range of national contexts. We analysed cross-sectional data gathered in 32 countries ( N  = 12, 246). Our results show that climate anxiety is positively related to rate of exposure to information about climate change impacts, the amount of attention people pay to climate change information, and perceived descriptive norms about emotional responding to climate change. Climate anxiety was also positively linked to pro-environmental behaviours and negatively linked to mental wellbeing. Notably, climate anxiety had a significant inverse association with mental wellbeing in 31 out of 32 countries. In contrast, it had a significant association with pro-environmental behaviour in 24 countries, and with environmental activism in 12 countries. Our findings highlight contextual boundaries to engagement in environmental action as an antidote to climate anxiety, and the broad international significance of considering negative climate-related emotions as a plausible threat to wellbeing. Highlights: This study examines negative emotional responses to climate change in 32 countries. Climate anxiety is positively related to pro-environmental behaviour and environmental activism. Climate anxiety is inversely related to mental wellbeing. Climate anxiety is more strongly related to pro-environmental actions in individualistic and wealthier countries.